2020
DOI: 10.1007/s00428-020-02818-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing agreement of breast cancer luminal molecular subtype by Ki67 labeling index between core needle biopsy and surgical resection specimens

Abstract: Reliable determination of Ki67 labeling index (Ki67-LI) on core needle biopsy (CNB) is essential for determining breast cancer molecular subtype for therapy planning. However, studies on agreement between molecular subtype and Ki67-LI between CNB and surgical resection (SR) specimens are conflicting. The present study analyzed the influence of clinicopathological and sampling-associated factors on agreement. Molecular subtype was determined visually by Ki67-LI in 484 pairs of CNB and SR specimens of invasive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…To date, few published articles have evaluated the prognostic value of Ki-67 change after CNB in untreated breast cancer patients ( 41 ). Previously, a small-sized study by Kristina A. Tendl-Schulz et al showed that agreement of Ki-67 level between biopsy and surgery did not significantly impact recurrence-free survival (RFS) or OS ( P = 0.22 for both) ( 41 ). Herein, we demonstrated in the large-scale cohort that Ki-67 change pattern after CNB was significantly associated with RFI and BCSS in HR+/HER2− breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few published articles have evaluated the prognostic value of Ki-67 change after CNB in untreated breast cancer patients ( 41 ). Previously, a small-sized study by Kristina A. Tendl-Schulz et al showed that agreement of Ki-67 level between biopsy and surgery did not significantly impact recurrence-free survival (RFS) or OS ( P = 0.22 for both) ( 41 ). Herein, we demonstrated in the large-scale cohort that Ki-67 change pattern after CNB was significantly associated with RFI and BCSS in HR+/HER2− breast cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that the Ki-67 expression levels are closely related to differentiation levels, infiltration, metastasis, and prognosis of rectal cancer and directly affect prognosis outcomes [ 9 , 10 ]. However, Ki-67 expression can only be determined through invasive biopsy or surgical pathology tissues [ 11 ]. Preoperative examination approaches assessing Ki-67 expression enabling to predict patient prognosis without having to undergo invasive examinations or surgery can thus be beneficial for patients.…”
Section: Introductionmentioning
confidence: 99%
“…stage: N0 (no positive lymph node), N1 (1-3 positive lymph node) or N2 (≥ 4 positive lymph node). It was considered positive if lymph node showed suspicious morphology (round shape, irregular border, heterogeneous signal) and short axis diameter > 9 mm[13];(11) enhancement pattern (EP): Mild/Moderate or obvious enhancement of tumor compared to normal rectal wall enhancement (Fig.2a,b); and (12) rM: presence of metastasis determined according to radiological examination. Discrepancies between the radiologists were resolved by consensus after joint re-evaluation of the images and confirmed by another radiologist with 20 years of experience in abdominal diagnosis.…”
mentioning
confidence: 99%
“…High Ki67 expression in PCa is a poor prognostic factor and is correlated with overall survival, disease-free survival, and distant metastasis [ 8 , 9 ]. The existing methods for detecting Ki67 expression levels are invasive, complex, barely reproducible, and susceptible to subjective influence [ 10 , 11 ]. Therefore, researchers must develop noninvasive, simple, and reproducible methods for detecting Ki67 expression in patients with PCa.…”
Section: Introductionmentioning
confidence: 99%